The Role of Women in Organizations Terrorism: Gender Dynamics in the Context of Ideology and Violence - Dyah Aryati Nugraha Ningsih; Fauzia Gustarina Cempaka Timur; Rudy Sutanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Global security studies are increasingly paying attention to the role of women in terrorism. For years, women were usually considered only as victims or supporters of terrorism. However, the role of women in terrorist organizations is much more complex. They do many things, from spreading ideology to carrying out acts of violence. There are those who categorize the role of women in terrorist groups based on their ideology, such as in terrorist groups that demand independence or send countries. In these circumstances, women are more likely to be responsible for operational tasks. The aim of this research is to analyze the role of women in terrorist organizations by placing special emphasis on gender dynamics in relation to ideology and acts of violence. The data collection method is descriptive qualitative, and literature study is used as the data collection method. The results of the analysis show that the role of women in terrorist organizations is not only as ordinary supporters, but also directly involved in violence and the spread of ideology. Often, women are used to carry out acts of terror, both as main agents and as support crew. Women play an important role in maintaining and spreading the ideology of terrorism in an ideological context. They assist in recruiting new members and engage in radicalization and indoctrination processes.